Personnel Information System Using Microsoft Excel (Case Study: Bima City Health Office) - Wulan Ramdhani; Arizona Firdonsyah (Universitas Muhammadiyah Sidoarjo, 2021)
Information system is a system that has the ability to collect information from all sources and use various media to display information. Microsoft Excel is a spreasheet application program (electronic worksheet), the function of Microsoft Excel is to perform calculation operations and can present data in table form, while the filter and sort data functions are used to sort or filter data, for example: the ascending function and descending to sort data from the largest or from the smallest, the Sort By and Sort On features, in addition to the filter function to display data with certain criteria, the filter feature function or often referred to as autofilter, which functions to display certain rows of data according to filters already applied and hides the rest of the remaining rows of data. This study aims to facilitate the search for staffing data at the Health Office of the City of Bima, the method of data collection using 2 methods, namely literature study and observation, the results of research that have been conducted are that there is no personnel information system because the process of searching and recording personnel data is still done manually.